Development of Website-based Virtual Science Learning to Train Students' Critical Thinking Skills - Putrianingtyas, Sinta; Dewi, Novi Ratna; Adriyani, Resti (Journal of Environmental and Science Education, 2022)
The main concept in education in the 21st century revolution 4.0 is a process or learning with the support of information technology. The 2013 curriculum is designed to develop the 21st century skills of students. One of them is critical thinking skills. Based on government policies issued by the Ministry of Education and Culture (Kemendikbud) Directorate of Higher Education No. 1 of 2020 which states that the learning process is carried out boldly (online). This is because to respond to the COVID-19 pandemic that has occurred throughout the world, none other than Indonesia. The LMS referred to in the research is the development of a website-based Virtual Science Learning or “VISEL” to train critical thinking skills. This study aims to develop an e-learning system called VISEL (Virtual Science Learning) based on a website that can be used to train students' critical thinking skills. The development procedure is carried out with reference to the development of a 4D model. The research data obtained were in the form of product validation score data, questionnaire readability data, and response questionnaire data. The results showed that after going through the product validation process, the material expert obtained an average percentage of 97%% with valid criteria. Product validation by media experts obtained an average percentage of 96% with valid criteria. The average readability questionnaire obtained 88.57% and was included in the very good category. The average payment from VISEL's response obtained an average of 95.46% and was included in the very good category.